2009
DOI: 10.1093/carcin/bgp101
|View full text |Cite
|
Sign up to set email alerts
|

Dietary flavonoid fisetin induces a forced exit from mitosis by targeting the mitotic spindle checkpoint

Abstract: Fisetin is a natural flavonol present in edible vegetables, fruits and wine at 2-160 microg/g concentrations and an ingredient in nutritional supplements with much higher concentrations. The compound has been reported to exert anticarcinogenic effects as well as antioxidant and anti-inflammatory activity via its ability to act as an inhibitor of cell proliferation and free radical scavenger, respectively. Our cell-based high-throughput screen for small molecules that override chemically induced mitotic arrest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 42 publications
2
40
0
1
Order By: Relevance
“…Geraldol has no known biological activity, but fisetin, a closely structurally related flavonoid that induces mitotic slippage less potently than geraldol ( Supplementary Fig. S3), has also been reported to inhibit Aurora B (30). Geraldol was assayed for in vitro inhibition of a panel of kinases including Src, Aurora A, and Aurora B (Supplementary Table S1) and showed significant inhibition of Aurora A and Aurora B but not Src.…”
Section: Inhibition Of the Aurora Kinases By Su6656 And Geraldolmentioning
confidence: 99%
See 1 more Smart Citation
“…Geraldol has no known biological activity, but fisetin, a closely structurally related flavonoid that induces mitotic slippage less potently than geraldol ( Supplementary Fig. S3), has also been reported to inhibit Aurora B (30). Geraldol was assayed for in vitro inhibition of a panel of kinases including Src, Aurora A, and Aurora B (Supplementary Table S1) and showed significant inhibition of Aurora A and Aurora B but not Src.…”
Section: Inhibition Of the Aurora Kinases By Su6656 And Geraldolmentioning
confidence: 99%
“…Our group and others have identified chemicals that stimulate mitotic slippage and observed that slipped cells typically undergo at least 1 round of DNA replication without subsequent cell division but that, eventually, all cells that undergo mitotic slippage die (26)(27)(28)(29)(30) (27), and fisetin (30); Supplementary Fig. S1].…”
Section: Introductionmentioning
confidence: 99%
“…Fisetin (3,3¢,4¢,7-tetrahydroxyflavone) is a natural flavonoid found in the smoke tree and is also widely distributed in various fruits and vegetables such as strawberry, apple, persimmon, grape, onion and cucumber [6]. Fisetin has been reported to exhibit a wide variety of activities, including neurotrophic, antioxidant, anti-inflammatory, antimetastatic and anti-angiogenic effects [7][8][9][10][11]. Moreover, it has been shown to suppress the proliferation and induce apoptosis of a wide variety of tumour cells, including prostate cancer, liver cancer, colon cancer, pancreatic cancer, hepatocellular cancer and leukaemia cells [12][13][14][15][16].…”
mentioning
confidence: 99%
“…1H), were found to potently suppress endogenous Aurora B activity [24,25]. Natural product Fisetin and Luteolin were also reported to inhibit Aurora B kinase activity in cancer cells [26,27]. In addition to AZD1152, AT9283, PHA-739358, MLN8237 and ENMD2076 (Fig.…”
Section: Introductionmentioning
confidence: 95%